Controlled-rocking Braced Frame Bearing on a Shallow Foundation. (November 2018) - Rahgozar, Navid; Rahgozar, Nima; Moghadam, Abdolreza S.
Abstract: Controlled-rocking braced frames are capable of reducing the drawbacks of conventional frames against seismic loading. This paper examines the effects of soil-foundation modeling on the seismic responses of low-rise controlled-rocking braced frames. For this purpose, dynamic analyses are performed on rocking braced frames and similar conventional frames supported on fixed base and flexible foundations. Structural modeling considerations such as nonlinear constitutive modeling of members, post-tensioned cables, and yielding butterfly-shaped fuses are modeled in OpenSees, and shallow foundations founded on the soil are simulated using the beam-on-nonlinear-Winkler-foundation approach. The effects of modeling and ground motion parameters on seismic performance are investigated from various aspects. Findings show significant foundation flexibility effects in rocking braced-frame archetypes.